Macroeconomic Issues in Small States and Implications for Fund Engagement. (Policy Papers; Policy Paper ;, 2013)
This paper reviews the macroeconomic characteristics and performance of small states and discusses ways in which the Fund's engagement with these countries could be better tailored to meet their needs. The Fund previously examined small states issues in 2000, informed by a Joint Task Force Report of the Commonwealth Secretariat (CS) and World Bank. Small states continue to face many of the same challenges they did then, and the 2000 Small States Report remains the foundation for much of the work in this area, both inside and outside the Fund. However, the relative macroeconomic performance of small states has deteriorated since the late 1990s, and a fresh look is warranted.